(untitled) (Revista de Estudos da Linguagem, 1995)
lnthe previous studies ofautosegmental phonology, the nasal harmony was considered as the universally conditionedharmony process, like tone, [±back], [ATR].lnthis paper, following the theory ofClements (1991), I propose that the language particular association convention should be assumed to explain the nasal harmony in Aguruna.